قدرة طلاب الصف الثامن A بالمدرسة المتوسطة الإسلامية YPII كوتاريح على نطق الأصوات العربية عند قراءة النص: ملخص, مقدمة, الدراسات السابقة, منهجية البحث , نتائج البحث و مناقشاتها , الخاتمة - Intan Fairuzzia Malini intan; Ahmad Zaky; Khairul Anhar (Al-Ahruf (Journal for Arabic and Linguistics Education), 2025)
The objectives of this research are to know the ability of eighth grade A students at Islamic Junior High School YPII Kotarih to pronounce Arabic sounds and to know the obstacles faced by eighth grade A students at Islamic Junior High School YPII Kotarih in pronunciation of Arabic sounds. This research is a qualitative research and the methodology used is the descriptive method. The data collection method is interview, observation and documentation. The data analysis method is based on the Miles and Huberman method.The conclusion of this research is 1) The ability of the students in the eighth grade A at the Islamic Junior High School YPII Kotarih to pronounce Arabic sounds is weak. 2) The obstacles that the students in the eighth grade A at the Islamic Junior High School YPII Kotarih faced in pronouncing Arabic sounds include the lack of desire and enthusiasm to study the Arabic language, and most of them did not study the Qur’an or study in the initial religious school when they were young.